Multiple surface plasmon excitations in overlayers of K and Na on Ru(001) - Zharnikov, M.; Mehl, D.; Steinrück, Hans-Peter (Journal of Electron Spectroscopy and Related Phenomena, 1994)
Electron energy loss spectra in the reflection geometry have been measured for potassium and sodium layers on Ru(001) for coverages ranging from N = 1 up to 16-20 layers. The experimental conditions (primary energy, angle-of-incidence) allowed excitation of multiple surface plasmons. For all systems, energy and damping of the surface plasmons together with the integral probability for surface plasmon excitation have been determined. For the variation of these parameters with alkali layer thickness, two coverage regimes can be distinguished that are correlated to different types of excitations. For N ≤ 1 one-electron excitations are very important; for N ≥ 2 a collective response (well-defined surface plasmon excitations) takes place. The slowly decreasing energy of the surface plasmon with increasing alkali thickness to the bulk values is in qualitative agreement with both macroscopic and microscopic descriptions. The thickness dependences of the damping and the integral excitation probability indicate that one-electron contributions which are very important for N = 1 are also present for N = 2 and only slowly decrease with increasing thickness of the alkali layer. The analysis of the EELS data for N ≥ 2 shows that the excitation probability for multiple surface plasmons follows the Poisson distribution; the data are consistent with the consecutive excitation of individual surface plasmons. © 1994.